ANALYSIS OF THE CURRENT STATE OF THE PROBLEM OF ENERGY SAVING IN HOUSING AND COMMUNAL SERVICES UKRAINE - , Д. С. (Municipal economy of cities (Technical science), 2013)
The dynamics of key indicators of energy consumption and energy intensity of GDP in Ukraine, revealed major potential for energy savings